2020
DOI: 10.1002/aenm.201904247
|View full text |Cite
|
Sign up to set email alerts
|

3,4‐Dicyanothiophene—a Versatile Building Block for Efficient Nonfullerene Polymer Solar Cells

Abstract: In this contribution, a versatile building block, 3,4‐dicyanothiophene (DCT), which possesses structural simplicity and synthetic accessibility for constructing high‐performance, low‐cost, wide‐bandgap conjugated polymers for use as donors in polymer solar cells (PSCs), is reported. A prototype polymer, PB3TCN‐C66, and its cyano‐free analogue polymer PB3T‐C66, are synthesized to evaluate the potential of using DCT in nonfullerene PSCs. A stronger aggregation property in solution, higher thermal transition temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 83 publications
0
35
0
Order By: Relevance
“…[ 58‐59 ] As an example, Zhang et al . [ 60 ] substituted the cyano group for the hydrogen group in PB3T‐C66 to obtain PB3TCN‐C66, and found that B3T‐C66 and PB3T‐C66:IT‐4F blends exhibited ε r of 2.75 and 2.54 at 1 kHz, respectively. In comparison, the cyano‐group based PB3TCN‐C66 donor and its blends with IT‐4F acceptor exhibited higher values of ε r of 4.31 and 3.60 at the same frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[ 58‐59 ] As an example, Zhang et al . [ 60 ] substituted the cyano group for the hydrogen group in PB3T‐C66 to obtain PB3TCN‐C66, and found that B3T‐C66 and PB3T‐C66:IT‐4F blends exhibited ε r of 2.75 and 2.54 at 1 kHz, respectively. In comparison, the cyano‐group based PB3TCN‐C66 donor and its blends with IT‐4F acceptor exhibited higher values of ε r of 4.31 and 3.60 at the same frequency.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, to increase the χ of the hyper-miscibility system PB3T-C66:IT-4F, Duan and coworkers introduced the cyano group to the donor PB3T-C66, improving the domain purity from 0.62 to 1, and significantly increasing the J SC and FF. [103] Finally, the PCE was increased from 2.3% to 11.2%. [103] From the perspective of the acceptor, Hou and coworkers changed the end group of BTP-4Cl to reduce its miscibility with P3HT.…”
Section: Morphology Controlmentioning
confidence: 99%
“…[103] Finally, the PCE was increased from 2.3% to 11.2%. [103] From the perspective of the acceptor, Hou and coworkers changed the end group of BTP-4Cl to reduce its miscibility with P3HT. [104] The enhanced χ of the system drives an appropriate phase separation, increasing the J SC and FF significantly.…”
Section: Morphology Controlmentioning
confidence: 99%
“…Polymer solar cells (PSCs) have achieved a huge breakthrough in the past 5 years with the combinational contributions from the developments of nonfullerene acceptors (NFAs), polymeric donors, and kind of redundant of device engineering. [ 1–12 ] Compared with traditional fullerene acceptors, A–D–A framework nonfullerene small molecular acceptors (NF‐SMAs) have significant advantages in broader absorption range, tunable molecular structure and energy levels, and diversified donor materials for matching. [ 13–23 ] Therefore, many such typed NF‐SMAs have been synthesized and become the mainstream materials for the development of high‐efficiency PSCs.…”
Section: Introductionmentioning
confidence: 99%